Analisis Pengakuan Beban Kontrak Konstruksi Berdasarkan PSAK NO. 34 pada Perusahaan Jasa Konsultansi Konstruksi: Studi Kasus PT. Ravino Citra Mandiri - Marchella Liu Josri; Icha Fajriana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze how the application and recognition of revenue and expenses in construction consulting service companies in accordance with PSAK No. 34 at PT Ravino Citra Mandiri. The data used for this research is secondary data in the form of records of PT Ravino Citra Mandiri's project expenses and revenues for the period July 2021 - December 2021. The method used for data collection is through interviews, observation and documentation. The data analysis technique uses qualitative analysis. The results showed that the application of PSAK No. 34 at PT Ravino Citra Mandiri was still not implemented in its entirety, where the recording was still carried out on a cash basis, but the recording and recognition of expenses was appropriate. The application of the work contract method is not yet appropriate, because the company only records using the cash basis system due to improper management so that the author presents a comparison if the recording is justified using the completed contract method and also the percentage of completion method, the percentage of completion method is used because the billing system carried out for the project uses a term system. The use of this method is considered by the company as a recording with a high accuracy value because it records all historical costs during the work of the work project compared to the completed contract which only records receipts and expenses for the work project.